Granulocytic Myeloid Derived Suppressor Cells Expansion during Active Pulmonary Tuberculosis Is Associated with High Nitric Oxide Plasma Level - El Daker, Sary; Sacchi, Alessandra; Tempestilli, Massimo; Carducci, Claudia; Goletti, Delia; Vanini, Valentina; Colizzi, Vittorio; Lauria, Francesco Nicola; Martini, Federico; Martino, Angelo (PLOS ONE, 2015)
Tuberculosis (TB) is still the principal cause of death caused by a single infectious agent, and the balance between the bacillus and host defense mechanisms reflects the different manifestations of the pathology. The aim of this work was to study the role of myeloid-derived suppressor cells (MDSCs) during active pulmonary tuberculosis at the site of infection. We observed an expansion of MDSCs in the lung and blood of patients with active TB, which are correlated with an enhanced amount of nitric oxide in the plasma. We also found that these cells have the remarkable ability to suppress T-cell response, suggesting an important role in the modulation of the immune response against TB. Interestingly, a trend in the diminution of MDSCs was found after an efficacious anti-TB therapy, suggesting that these cells may be used as a potential biomarker for monitoring anti-TB therapy efficacy.